Failure investigation of internal dragline dump slope - A case study - Rai R.; Singh V.K.; Singh S.; Maji V.B. (My University, 2025)
The stability of internal mine waste dump is plays an important in the economics and also safety point of view. The failure in internal dump slopes leads to loss of life, production and serious impact on surrounding facilities. The internal dumps are usually consisting of a mixture of fragmented rocks and loose material. The present paper discussed the failure case of internal dragline dump of an opencast mine “A” using limit equilibrium and finite element method. The failed dragline overburden dump found to displace the coal rib along with overburden material approximately 80m from the original location of toe of the coal rib. The location of failure plane has been determined and found to be through the base of the coal rib left adjacent to the dragline dump during extraction of coal. Copyright © Soil Mechanics and Geotechnical Engineering, ARC 2019.All rights reserved.